2011
DOI: 10.2109/jcersj2.119.486
|View full text |Cite
|
Sign up to set email alerts
|

Development of new solution method using citric acid and ethylenediamine for borate compounds

Abstract: A new solution method that can be used to synthesize borate compounds was developed using citric acid and ethylenediamine. The conventional polymerizable complex method (polyester method) has a significant advantage in terms of homogeneity of the precursor, and it has been utilized in the synthesis of numerous oxide ceramics. However, it is very difficult to synthesize borate compounds by the conventional polymerizable complex method because boron reacts with the glycol that is necessary for the polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…No secondary phase was detected for the pure powders. Matsumoto et al reported the differential thermal analysis curve and XRD patterns for InBO 3 obtained via the citric acid method at 1000 1C with 5 mol% excess H 3 BO 3 [20]. In the present study, the InBO 3 nanocrystals were prepared at a lower temperature (6001C).…”
Section: Experimental Methodsmentioning
confidence: 77%
“…No secondary phase was detected for the pure powders. Matsumoto et al reported the differential thermal analysis curve and XRD patterns for InBO 3 obtained via the citric acid method at 1000 1C with 5 mol% excess H 3 BO 3 [20]. In the present study, the InBO 3 nanocrystals were prepared at a lower temperature (6001C).…”
Section: Experimental Methodsmentioning
confidence: 77%